Rotating-pulling-poking manipulation effectively alleviates pain symptoms of lateral ankle sprain: an animal experimental study - Wen, Haibao; Gao, Jinghua; Shi, Fudong; Li, Jin; Fu, Minrui; Feng, Minshan; Li, Luguang; Gao, Chunyu; Li, Jianguo (Frontiers in Pain Research, 2025)
This study aimed to explore the analgesic mechanism of the Rotating - Pulling - Poking Manipulation in treating acute lateral ankle sprain (ALAS). Thirty rats were randomly divided into 5 groups in the first experiment to determine the dose - effect relationship by detecting ankle pain thresholds at different time points. The results showed that the 5-min manipulation group had the best analgesic effect, with the bipedal weight - bearing difference decreasing over time and pain relief time shortened. In the second experiment, 30 rats were divided into 3 groups. After manipulation, samples from PAG and RVM were tested. The results indicated that compared with the model group, the 5-min manipulation group had increased MOR expression in PAG and 5 - HT concentration in cerebrospinal fluid, decreased expressions of BDNF, p - TrkB/TrkB in PAG and NR2A in RVM, and reduced contents of IL - 6, IL - 1β, TNF - α in ankle soft tissues. In conclusion, the Rotating - Pulling - Poking Manipulation can relieve pain by exciting the descending inhibitory system mediated by opioid receptors in the brain center, weakening the descending facilitation system mediated by the BDNF/TrkB/NR2A signaling pathway, and reducing the inflammatory response.